THE USE OF PER SE ILLEGAL APPROACH IN PROVING THE PRICE-FIXING AGREEMENTS IN INDONESIA - Anisah, Siti (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
The Indonesia Competition Commission (the ICC) often faces difficulties to find evidence in the form of agreement made by business actors in determining prices. The agreement is the main element to prove the price-fixing which is prohibited under Article 5 of Law No. 5 of 1999. The legal issue discussed in this research is whether the use of per se illegal approach in proving the price-fixing agreement requires direct evidence or it is sufficient with an indirect evidence. This normative study found that the competition authorities still impose sanctions to business actors even though the (legitimate) agreement does not exist. The examination requires an in-depth understanding of economic theories and should prioritize the principle of prudence due to its vulnerability to manipulation. The analysis of Decision No. 08/KPPU-I/2014 and 04/KPPU-I/2016 found that the ICC proved the price-fixing case using indirect evidence and included an analysis of the impact on competition. Both cases indicate that the ICC applied the rule of reason approach because of the difficulties in finding the evidence of the agreement. On the other hand, the ICC applied per se illegal approach in the Decision No. 10/KPPU-L/2009 and 14/KPPU-I/2014 due to the existence of direct evidence.